Follow‐up of the re‐evaluation of glycerol esters of wood rosins (E 445) as a food additive - EFSA Panel on Food Additives and Flavourings (FAF); Maged Younes; Gabriele Aquilina; Gisela Degen; Karl‐Heinz Engel; Paul Fowler; Maria Jose Frutos Fernandez; Peter Fürst; Rainer Gürtler; Trine Husøy; Melania Manco; Wim Mennes; et al. (EFSA Journal)
Abstract Glycerol esters of wood rosin (GEWR) (E 445) were re‐evaluated in 2018. On the toxicity database and given the absence of reproductive and developmental toxicity data, the acceptable daily intake (ADI) of 12.5 mg/kg body weight (bw) per day for GEWR (E 445) established by the Scientific Committee on Food (SCF) in 1994 was considered temporary. The conclusions of the assessment were restricted to GEWR derived from Pinus palustris and Pinus elliottii and with a chemical composition in compliance with GEWR used in the toxicological testing. Following a European Commission call for data to submit data to fill the data gaps, the present follow‐up opinion assesses data provided by interested business operators (IBOs). Considering the technical data submitted by IBOs, the EFSA Panel on Food Additives and Flavourings (FAF Panel) recommended some modifications of the existing EU specifications for E 445, mainly a revision of the definition of the food additive and lowering the limits for toxic elements. Considering the available toxicological database evaluated during the re‐evaluation of E 445 by the ANS Panel in 2018, and the toxicological studies submitted by the IBOs, the Panel established an ADI of 10 mg/kg bw per day based on the no observed adverse effect level (NOAEL) of 976 mg/kg bw per day from the newly available dietary reproduction/developmental toxicity screening study in rats and applying an uncertainty factor of 100. Since GEWR from P. palustris and P. elliottii were tested in the toxicity studies considered to establish the ADI and in the absence of detailed information on the chemical composition (major constituents) in GEWR generated from other Pinus species, thus not allowing read across, the ADI is restricted to the GEWR (E 445) manufactured from P. palustris and P. elliottii. The Panel concluded that there was no safety concern for the use of GEWR (E 445), at either the maximum permitted levels or at the reported uses and use levels.